Aerobics research in China: characteristics, hotspots, and evolution visualized - Yang, Wang; Zainuddin, Zainal Abidin B (International Journal of Public Health Science (IJPHS), 2025)
This study utilizes CiteSpace software to visually analyze 679 core journal papers from the CNKI database, exploring the landscape of aerobics research in China. It aims to identify influential authors and institutions while elucidating the evolution of research focus from its early stages to current trends. The primary objective is to explore the characteristics of aerobics research, including hot topics, evolving frontiers, and key developments. By examining titles, keywords, abstracts, and other materials, CiteSpace software provides insights into the scientific knowledge graph, emphasizing influential authors and institutions in aerobics research. The findings reveal a notable shift in focus from early public teaching to current emphasis on competitive aerobics, physical education, and athlete transitions. The research field has expanded to encompass diversified topics, showcasing continuous depth in empirical and theoretical investigations. Three distinct periods are identified in research frontiers: early, middle, and recent stages, each with unique directions and emphases. The study recommends a multi-disciplinary integrated development approach in aerobics research, emphasizing enriched teaching and competition visions, improved regional integration policies, and a comprehensive display of the field’s research and development status. Acknowledging evolving trends and diversification will contribute to a holistic understanding and continued advancement of aerobics research.